Gastos deducible y no deducible y su incidencia en la situación económica y financiera de la empresa Multiservicios Ticla SAC, periodo 2012 - 2013 - Ramírez Vela, Jhon Hans (2015)
To determine the deductible and nondeductible expenses and determine their impact on the economic and financial situation of the company MULTISERVICIOS TICLA SAC 2012 - 2013. The research method is the inductive is one that is one scientific method that obtains general conclusions from particular premises. This is the more usual scientific method , which can distinguish four essential steps : observation of facts for registration ; classification and study of these facts; inductive derivation of the facts and lets get to a generalization ; and calibration. Observed phenomena as they were in their natural context and then analyze them as was the case of deductible and non -deductible expenses and their impact on the economic and financial situation of the company MULTISERVICIOS TICLA SAC. The relationship needs to be established between expenditures and income generation or maintenance of the source, a notion that our legislation is broad in nature because subtracting expenses that bear no direct relationship that is allowed; notwithstanding this the causality principle must be attended to, so to be given additional criteria shall apply as that expenditure is normal according to the business or they maintain some proportion to the volume of transactions among others. The company does not take control over the deductible expenses with limits have been sustained excess costs with sales Ballots may be deductible in determining net income for the third category , expenditures on vehicles , lease expense , the limit is not applied when were treated for travel expenses , that the review has generated a tax on higher income as declared .